Conceptual design of removable fixed platform in Gulf of Thailand - Nattakarn Wongrod; Chiu, Gregory L.F.; Pornpong Asavadorndeja; Thongchai Phanyasahachart; RTG Fellowship (Pathumthani : Asian Institute of Technology, 2013)
This thesis presents the study of possibility of providing innovative design methods of fixed wellhead platform structure to develop the marginal oil and gas fields in Gulf of Thailand (GoT). The key characteristics of the removable platform concept are not only optimal size and weight but also able in practical work. The conceptual of this study is to joining two components of an offshore platform in the water to form a single jacket unit in view of practical work and optimal cost. This platform is able to re-deploying and can be re-using for the production of oil or gas in the new site. This study proposed six types of different structures of removable fixed platform. The conceptual of the designs are distributed by the foundation system conditions are namely: suction plie and cluster pile concept. In each foundation system are divided to three types of the connection design. The proposed three connection models are namely: weld connection, mechanical connection, and self-installation lock connection. The proposed sixe models were carried out by performing Quasi-static in-place analysis to verify the structural strength and serviceability of these platforms in designed water depth 80 m. The platforms are subject to environmental load of 1-year return period and 100 year return period for operating and extreme storm conditions, respectively. Three concepts of transportation, installation, and re-deploying concepts are developed and assessed the cost. It can be drawn from the results that two of these foundation system of wellhead platform configurations are able to install, re-deploy and suitable in the marginal field in the GoT by using these three installation concepts. Suction piles can be used as the new foundation concept of the removable wellhead platform structures. Avoiding the use of hammer vessel and suitability to install the support structure of a platform with the minimize installation timing are the advantages in this concept. Moreover, suction pile is possible to re-deploying itself to the new location. Self-installation lock concept, this concept advantages are the most that had simple installation/un-installation equipment and ease to installation/un-installation for re-deploying to the new location. Nevertheless, the conceptual designs still has some issue for further research by performing the laboratory test or field test verification the connection strength capacity. However, in view of connection concepts, the connection conceptual designs still able to develop to suitable in the shallow water or deeper water in the further.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Offshore Technology and Management,School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2013
Keywords: Offshore structures -- Materials -- Thailand, Gulf of; Offshore oil industry -- Design and construction -- Thailand, Gulf of